Synthesis, Structure, and Ligand Exchange Reactions of Tetramethyleneethane Complexes of Cobalt - Aguirre-Etcheverry, P; Ashley, A; Balazs, G; Green, J; Cowley, A; Thompson, A; O'Hare, D (2010)
The synthesis of (η3:η3-TME)[Co(CO) 3]2 (1) was achieved using 2,3-bis(bromomethyl)-1,3- butadiene (TMEBr2) as the tetramethyleneethane (TME) ligand precursor and Na[Co(CO)4]. Solution NMR studies suggested an η3:η3-configuration, which has been confirmed in the solid state by single-crystal X-ray diffraction studies. The series of complexes (η3:η3-TME)[Co(CO)2PR 3]2 (R = Me, 2; R = Et, 3; R = n-Bu, 4; R = Ph, 5; R = OPh, 6) were also synthesized by ligand exchange reactions, demonstrating that only one carbonyl may be exchanged for a phosphine group on each metal center. The η3:η3-configuration of the tetramethyleneethane ligand in these complexes was determined by crystallographic studies. The effect of the electron-donating properties of PR3 was studied by cyclic voltammetry (CV) and infrared spectroscopy. The greatest degree of electron donation was seen when R = Et (3) and lowest when R = Ph (5) or R = OPh (6). Electronic communication between the metal centers was observed by CV. The chemical oxidation of 1 resulted in a highly unstable species that decomposed to {[(CO)2Co]TME[Co(CO) 3]}+[BF4]- (1+d), determined by its crystal structure. The synthesis of (η4: η4-TME)[CoCp*]2 (7) has been achieved using a dipotassium 2,3-bis(methylene)-1,3-butanediyl (TMEK2) synthon. NMR studies suggested that 7 adopts an unusual η4:η4- configuration, which was confirmed with the aid of crystallographic studies. DFT calculations were performed in order to rationalize the bonding for 1, 7, and hypothetical (η4:η4-TME)[CoCp]2 (8). The large energy difference between the two coordination isomers 1 and 1a confirmed the η3:η3-configuration. For isomers 7/7a and 8/8a, the energy difference between the two isomers (ca. 15 kJ mol -1) is in favor of the η4:η4- configuration. For complexes 1+ and 8+, the calculations suggested complete delocalization on the system when one electron was removed. © 2010 American Chemical Society.